Factors Influencing Anxiety in Breast Cancer Patients Undergoing Chemotherapy - Rosliana Dewi; Ika Tarwiyah; Abdul Rahman La Ede; Johan Budhiana; Fera Melinda; Rakanda Putra Waliyu (Indonesian Journal of Global Health Research, 2025)
Breast cancer is the most common type of cancer in women and the leading cause of cancer death. In Indonesia, there were 65,858 new cases with 22,430 deaths, and a prevalence of 148.11 per 100,000. Chemotherapy is one of the popular therapy options among the public. Chemotherapy can lead to psychological impacts, such as stress, anxiety, and depression in breast cancer patients. Objective: This study aims to analyze the factors that influence anxiety in breast cancer patients undergoing chemotherapy at the Chemotherapy Poly of Bogor City Hospital. Methods: This cross-sectional study involved 87 breast cancer patients undergoing chemotherapy at the Chemotherapy Clinic of Bogor City Hospital who were selected using accidental sampling. Data were collected through a validated structured questionnaire, including anxiety felt by breast cancer patients which refers to the standardized questionnaire, namely the Zung Selfrating Anxiety Scale (ZSAS). Data were analyzed using chi-square test and logistic regression to identify the relationship between variables. Results: The results of the analysis showed a significant relationship between age (p = 0.000 OR = 14.625), education (p = 0.022, OR = 3.506), length of suffering (p = 0.000, OR = 0.208), and frequency of chemotherapy (p = 0.021, OR = 0.357) with anxiety of breast cancer patients. The most dominant variable associated with anxiety of breast cancer patients is age (OR = 35.934). Conclusion: Age, education, duration of breast cancer, and frequency of chemotherapy play an important role in influencing the anxiety of breast cancer patients.